A&T Ethiopia Adolescent Nutrition Endline Survey 2021: Parent - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
Alive & Thrive (A&T) is an initiative that supports the scaling up of nutrition interventions to save lives, prevent illnesses, and contribute to healthy growth and development through improved maternal nutrition, breastfeeding, and complementary feeding practices. In Ethiopia, A&T implemented a package of adolescent nutrition interventions through school-based (nutrition messages during flag assemblies, classroom lessons on nutrition, student clubs on nutrition for girls, peer mentoring on nutrition, body mass index (BMI) measurement with counseling, and parents’ meetings) and community platforms (health post and home visits and community gatherings to discuss adolescent nutrition). This dataset is part of a survey that was conducted to gather endline data for the impact evaluation of the interventions. The overall study objective was to determine the feasibility of delivering nutrition interventions primarily through school-based platforms and their impact on diet quality among adolescent girls. Research questions include: 1) What is the program impact on the diet of adolescent girls: (1) dietary diversity, (2) meal frequency, and (3) less consumption of unhealthy snacks? 2) What is the exposure to adolescent nutrition interventions delivered through school-based platforms? 3) What factors influenced the integration of adolescent nutrition interventions into school-based platforms and their outcomes?